EQUALIZATION AND EMPOWERMENT CULTURE OF WOMEN IN THE QUR’AN - Hossain, Md. Kohinoor (International Journal of Shari'ah and Corporate Governance Research, 2023)
Let's hear, people, brothers, and sisters. Human beings are the most truthful of all things on the earth. Nothing is above them. Among people, women are the most compassionate. Half of the world's population are women. Women are not simply beings who give birth to men, women, and those of a third gender. All men, women, and those of a third gender are one community. The entirety of human society trusts in various religions, folk religions, cultures, thoughts, and philosophies. All faiths have considered women as disregarded, obnoxious, incompetent, and sinful doers. They have been confined to women within four walls and have dominated them for a very long time. Only the divine and religious book, the Qur’an, has given women equality, empowerment, and dignity. Women have a long, strong, and proud history in human civilization. They are the chief mothers of world civilization. From the ground to the sky, women have worked as the founders of every society. Today, the world's superpowers do not desire full and equal women empowerment. They talk about women’s leadership at the round table but do not expect it in practice. Only the Qur’an desires to equalize and empower women from the beginning of human creation and livelihood on earth. This paper indicates the theological aspect and may be discussed as an academic study. No other religions or divine books foresee that women would lead all sectors of the world as men do. This paper attempts to prove that the Qur’an has fostered a culture of equalization and empowerment of women in all sectors of the earth.